2015
DOI: 10.1155/2015/927973
|View full text |Cite
|
Sign up to set email alerts
|

Personal Prayer in Patients Dealing with Chronic Illness: A Review of the Research Literature

Abstract: Background. Prayer is commonly used among patients for health purposes. Therefore, this review focused on three main questions: (1) why do people turn to prayer in times of illness?, (2) what are the main topics of their prayers?, and (3) how do they pray? Method. We undertook a systematic review of the literature by searching the databases PubMed, Medline, and PsycINFO. The following inclusion criteria were used: (1) participants in the study were patients dealing with an illness, (2) the study examined the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 37 publications
0
42
0
4
Order By: Relevance
“…It is quite interesting that participants overall perceive a greater need to "pray on one's own" rather than to "be prayed for" or to "pray with someone". In a literature review of chronically ill patients and prayer, the authors found that prayer, although focused on illness, was not used merely in hopes of being healed but rather as a resource to positively transform the experience of their illness (Jors et al 2015). Perhaps for this reason, personal prayer is viewed as providing a greater source of comfort.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite interesting that participants overall perceive a greater need to "pray on one's own" rather than to "be prayed for" or to "pray with someone". In a literature review of chronically ill patients and prayer, the authors found that prayer, although focused on illness, was not used merely in hopes of being healed but rather as a resource to positively transform the experience of their illness (Jors et al 2015). Perhaps for this reason, personal prayer is viewed as providing a greater source of comfort.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, people who rely on theistic beliefs may pray for various reasons: to connect with the Sacred (communication), to become healthy again (invocation), or to articulate fears and worries without any further expectation of healing (which nevertheless may result in feelings of relief). Interestingly, research on this topic has shown that most patients with chronic diseases pray with the intention of finding relief from their suffering; they do not necessarily pray to receive healing, but to "positively transform the experience of their illness" [7].…”
Section: Introductionmentioning
confidence: 99%
“…The volume of research on religiosity/spirituality and prayer, and their use in clinical practice, is still small [26]. The present article only mentions various aspects, which deserve an in-depth investigation, with an aim to further our understanding of the religious experience of the contemporary subject, and to discuss the validity, necessity, and challenges involving the integration of religious/spiritual dimensions into health care and clinical practice.…”
Section: Discussionmentioning
confidence: 98%